2021
DOI: 10.3390/en14041012
|View full text |Cite
|
Sign up to set email alerts
|

Energy and Economic Assessment of Energy Efficiency Options for Energy Districts: Case Studies in Italy and Egypt

Abstract: In this research, a technoeconomic comparison of energy efficiency options for energy districts located in different climatic areas (Naples, Italy and Fayoum, Egypt) is presented. A dynamic simulation model based on TRNSYS is developed to evaluate the different energy efficiency options, which includes different buildings of conceived districts. The TRNSYS model is integrated with the plug-in Google SketchUp TRNSYS3d to estimate the thermal load of the buildings and the temporal variation. The model considers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Calise et al [178] presented a technoeconomic comparison regarding various efficiency options (solar-energy technologies, improvements in building envelop in Naples (Italy) and Fayoum (Egypt) with dynamic estimation models in a T environment. The paper proposed an innovative system including a district network for hot water production and a space-heating strategy.…”
Section: Development Of District Heating Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Calise et al [178] presented a technoeconomic comparison regarding various efficiency options (solar-energy technologies, improvements in building envelop in Naples (Italy) and Fayoum (Egypt) with dynamic estimation models in a T environment. The paper proposed an innovative system including a district network for hot water production and a space-heating strategy.…”
Section: Development Of District Heating Systemmentioning
confidence: 99%
“…Calise et al [178] presented a technoeconomic comparison regarding various energyefficiency options (solar-energy technologies, improvements in building envelopes, etc.) in Naples (Italy) and Fayoum (Egypt) with dynamic estimation models in a TRNSYS environment.…”
Section: Development Of District Heating Systemmentioning
confidence: 99%
“…Results also indicated that the electrical efficiency was around 15.1% and the system presented clear advantages to buildings, essentially due to the electrical power generated by PV modules, also to participate to heat the adjacent zone to the building. A dynamic simulation model based on TRNSYS to assess different options of energy efficiency, primary saving of energy, payback period, and CO 2 emissions including different buildings in various districts i.e., Naples in Italy and Fayoum in Egypt, was developed [132]. The model included the energy balance for transient operation, while incorporating the geometrical building envelope.…”
Section: Overview Of Bipv Systemsmentioning
confidence: 99%
“…These studies also refer to various regional levels. For example, Calise et al [51] assesses different energy efficiency measures from a technological and economic point of view for two cities in Italy and Egypt, Nasirov et al [52] evaluates the macroeconomic impacts of different carbon phaseout trajectories for the Chilean economy, while Gonzalez-Salazar et al [53] examines the feasibility and potential of different coal phase-out scenarios in Berlin.…”
Section: Relevant Workmentioning
confidence: 99%